2016
DOI: 10.1038/ismej.2015.226
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between hydrology and water chemistry shape bacterioplankton biogeography across boreal freshwater networks

Abstract: Disentangling the mechanisms shaping bacterioplankton communities across freshwater ecosystems requires considering a hydrologic dimension that can influence both dispersal and local sorting, but how the environment and hydrology interact to shape the biogeography of freshwater bacterioplankton over large spatial scales remains unexplored. Using Illumina sequencing of the 16S ribosomal RNA gene, we investigate the large-scale spatial patterns of bacterioplankton across 386 freshwater systems from seven distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
203
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 178 publications
(236 citation statements)
references
References 54 publications
20
203
3
Order By: Relevance
“…400 streams, rivers and lakes), its role as a driver of taxonomic differences was much more important in large rivers and lakes than in headwater streams where water residence times are shorter. The observed response to pH in fast-flowing streams was interpreted as a signature of the landscape past environmental conditions (Niño-García et al, 2016a) rather than to in-stream selection. Since this was done considering the overall communities, which harbour both types of populations, it is possible that more clear links between environmental drivers and taxonomy will appear considering the two populations separately.…”
Section: Contrasting Dynamics and Environmental Controls Of Dispersedmentioning
confidence: 99%
See 4 more Smart Citations
“…400 streams, rivers and lakes), its role as a driver of taxonomic differences was much more important in large rivers and lakes than in headwater streams where water residence times are shorter. The observed response to pH in fast-flowing streams was interpreted as a signature of the landscape past environmental conditions (Niño-García et al, 2016a) rather than to in-stream selection. Since this was done considering the overall communities, which harbour both types of populations, it is possible that more clear links between environmental drivers and taxonomy will appear considering the two populations separately.…”
Section: Contrasting Dynamics and Environmental Controls Of Dispersedmentioning
confidence: 99%
“…In this regard, Crump et al (2007) suggested that bacteria transported by advection from upstream sources should constitute a small fraction of the total cells in systems with water residence times longer than bacterial doubling times. Other studies have explicitly explored the dynamics of different groups of bacterial taxa, showing that, whereas communities at the origin of the hydrologic continuum (i.e., in the smallest headwater streams) are mostly dominated by taxa washed from soils that likely cannot thrive in aquatic systems, downstream systems with longer water residence times mostly comprise typical freshwater taxa adapted to local conditions (Savio et al, 2015;Ruiz-González et al, 2015a;Niño-García et al, 2016a). Related to this, Niño-García et al, (2016a) found that, although pH seemed to shape bacterial communities along the whole aquatic continuum in the boreal landscape (ca.…”
Section: Contrasting Dynamics and Environmental Controls Of Dispersedmentioning
confidence: 99%
See 3 more Smart Citations